The Role of Husbands’ Support in the Selection of Intrauterine Device (IUD) Contraception in Primary Healthcare Settings: A Literature Review - Putri, Devia Lydia; Nuraida , Ida; Sartika, Sartika; Wahdiatis, Wahdiatis; Muharam, Raissya Farhani; Auladina, Siti Salwa (Ahmar Metastasis Health Journal, 2025)
The intrauterine device (IUD) is a highly effective long-acting contraceptive method; however, its utilization in primary healthcare settings remains relatively low. One of the key factors influencing decision-making regarding IUD use is husbands’ support. This study aimed to systematically identify and synthesize the role of husbands’ support in the utilization of IUD contraception at primary healthcare centers (Puskesmas). This study employed a narrative literature review with quantitative evidence synthesis, conducted systematically in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were performed in Google Scholar, Garuda, SINTA, and university repositories for articles published between 2021 and 2025. Of the 66 articles initially identified, title and abstract screening followed by full-text eligibility assessment based on predefined inclusion criteria resulted in six cross-sectional studies being included in the analysis. The findings demonstrated that all reviewed studies reported a statistically significant association between husbands’ support and IUD use (p < 0.05), with odds ratios ranging from 1.214 to 7.713. The variation in effect sizes indicates that husbands’ support functions as a reinforcing factor to a key determinant in contraceptive decision-making, depending on social context and regional characteristics. It can be concluded that husbands’ support is a critical determinant of IUD utilization in primary healthcare centers. These findings underscore the strategic role of primary healthcare centers in strengthening couple-based family planning programs through education and counseling interventions that actively involve husbands.